2023
DOI: 10.1186/s40104-023-00911-7
|View full text |Cite
|
Sign up to set email alerts
|

Implications of vitamin D for flesh quality of grass carp (Ctenopharyngodon idella): antioxidant ability, nutritional value, sensory quality, and myofiber characteristics

Yao Zhang,
Chaonan Li,
Xiaoqiu Zhou
et al.

Abstract: Background Muscle represents a unique and complex system with many components and comprises the major edible part of animals. Vitamin D is a critical nutrient for animals and is known to enhance calcium absorption and immune response. In recent years, dietary vitamin D supplementation in livestock has received increased attention due to biological responses including improving shear force in mammalian meat. However, the vitamin D acquisition and myofiber development processes in fish differ fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Dietary carnosine supplementation improved the thigh muscle meat quality in broilers, which was associated with the myofiber type conversion and composition, as well as better antioxidant capacity [ 9 ]. Overall, meat quality is connected with antioxidant capacity and myofiber characteristics [ 18 , 20 ]. Although our former study indicated that COS supplementation could enhance meat quality in broilers, there is little information available concerning the effects of COS supplementation on myofiber type conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary carnosine supplementation improved the thigh muscle meat quality in broilers, which was associated with the myofiber type conversion and composition, as well as better antioxidant capacity [ 9 ]. Overall, meat quality is connected with antioxidant capacity and myofiber characteristics [ 18 , 20 ]. Although our former study indicated that COS supplementation could enhance meat quality in broilers, there is little information available concerning the effects of COS supplementation on myofiber type conversion.…”
Section: Introductionmentioning
confidence: 99%